Lixiviados del relleno de residuos sólidos y sus efectos en la calidad del agua del estero Tonto Mal. Cantón la Maná. Año 2013. Propuesta Planta de tratamiento de lixiviados - Cedeño Muñoz, Ramiro Ignacio (2015)
The titled investigation work was Solid Waste Landfilling Leached and their Effects in the Quality of Water of the "Tonto Mal" Tideland, had with the purpose settled down of to accept or to reject the hypothesis that the mentioned liquids negatively affect to the quality of the water of this water stream. For it, were taken samples in the corresponding pool, particularly to the exit of the discharge to the tideland, for laboratory analysis, being determined the values means of the considered pollution indicative parameters contamination, that is, pH, dissolved Oxygen, SST, SDT, DBO, organic Nitrogen, Chlorides, Sulfates and, the metals heavy Iron, Chromium, Nickel, Lead, Zinc and Copper. The flow of leached entering to the tideland was determined by means of the seating capacity method, with a graduate recipient of 10 dm3 of volume and a digital chronometer. For the dependent variable or effect of the problem, it was sampled the waters of the tideland up and below (150 and 200 m) of the impact, being averaged the laboratory analysis obtained values. Afterwards it was calculated and selected a sample from population, in order to apply an interview guide, and being discussed the results through the analysis and the synthesis. Although the waters of the tideland already present certain levels of contamination before being impacted by those leaches, these affect their quality negatively, according to most of the parameters of the investigated contamination, for what was accepted, with enough level of trust, the hypothesis of outlined investigation. As solution proposal to the problem, a treatment system was designed for those leaches gathered consistent in dilution, anaerobic digestion and activated sludge system (with secondary sedimentation).